Perspectives on sexual and reproductive health self-care among women, healthcare providers, and other key informants: a mixed-methods study in South Africa and Zambia - Alice F. Cartwright; Marissa Velarde; Mags Beksinska; Jennifer Smit; Margaret Kasaro; Jennifer H. Tang; Cecilia Milford; Virginia Maphumulo; Manze Chinyama; Esther Chabu; Mayaba Mudenda; Christina Wong; et al. (BMC, 2023)
Abstract Background "Self-care" for sexual and reproductive health (SRH) includes contraceptive methods and other supplies that people can use with or without the support of a healthcare provider. Self-administered tests, self-injection of injectable contraception, or self-removal of intrauterine devices (IUDs) can increase people's access to and autonomy over their own SRH. Objectives of this study were to assess women's current interest in and use of SRH self-care and explore key informants' (KI) opinions of self-care, especially during the COVID-19 pandemic. Methods Data for this study came from female participants in the longitudinal Contraceptive Use Beyond ECHO (CUBE) study, and KIs, including healthcare providers, in South Africa and Zambia between September 2020 and June 2021. For this analysis, we used data from a participant phone survey (n = 537), and from in-depth interviews (IDIs) completed with a sub-sample of women (n = 39) and KIs (n = 36). Survey data were analyzed with descriptive statistics, and IDI data were analyzed using applied thematic analysis. Results Female survey participants in South Africa were more interested in learning about emergency contraceptive pills, subcutaneous injectable contraception, and CycleBeads, while Zambian participants wanted more information and access to condoms. However, in IDIs in both countries, women described minimal experience with self-care beyond condom use. In the Zambian KI IDIs, COVID-19 led to increased self-care counseling on subcutaneous injectable contraception and HIV self-testing. KIs who do not counsel on self-care were concerned that women may harm themselves or blame the provider for difficulties. Two KIs thought that women could possibly self-remove IUDs, but most expressed concerns. Reported barriers to self-care included COVID movement restrictions, transport costs, lack of accessible pharmacies, women's low awareness, and possible stigma. Conclusions Women surveyed reported interest in learning more about SRH self-care methods and resources, but in IDIs did not report extensive previous use besides condoms. KIs described some concerns about women's ability to use self-care methods. Counseling on and provision of self-care methods and supplies may have increased during the COVID-19 pandemic, but ensuring that self-care is more than just a temporary measure in health systems has the potential to increase access to SRH care and support women's autonomy and healthcare needs.